Nutritional status in patients with cystic fi brosis before and after lung transplantation - M. Sh. Khubutiya; M. E. Il'inskiy; A. A. Ryk; Yu. N. Lyashchenko (Трансплантология (Москва), 2017)
This review focuses on the nutritional status of patients with cystic fibrosis, systematic approach to monitoring and nutritional intervention in undernourished patients, and the maintenance of nutritional status before/after lung transplantation.